Moses Dobruska and the Invention of Social Philosophy Utopia, Judaism, and Heresy under the French Revolution - Greco, Silvana (De Gruyter, 2022)
Moses Dobruska, born as a Jew in Brno, Moravia in 1753, died on the guillotine in Paris in 1794. His life was adventurous, but the biography is not enough to understand the creative force of this atypical intellectual. Silvana Greco, sociologist of culture and Judaism, brings to the forefront the innovative contribution of the Philosophie sociale and highlights its fundamental role for the origins of sociological thought.